2022
DOI: 10.3390/heritage5040212
|View full text |Cite
|
Sign up to set email alerts
|

Underneath the Purple Stain

Abstract: The Alcobacenses are one of the most important Portuguese collections of Monastic codices. During a campaign study to further advance our knowledge on this important legacy and its state of conservation, a heavily deteriorated codex (ALC.338) stood out due to the presence of purple stains on the lower margins on virtually all folios. In some of them, the purple stains are accompanied by yellow and brown patches as well. Also noticed was the presence of these purple spots on the white tawed leather covering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is also found within other warm-blooded animals [77]. Although Malassezia is an unusual contaminant in cultural heritage, recent studies have revealed its unexpected presence on cultural heritage artifacts, such as ancient manuscripts, paintings, sculptures, photograph, and textiles [78,79]. The presence of this fungus on such objects poses new challenges for conservators and researchers due to its ability to degrade cellulose and produce lipolytic enzymes [80].…”
Section: Discussionmentioning
confidence: 99%
“…It is also found within other warm-blooded animals [77]. Although Malassezia is an unusual contaminant in cultural heritage, recent studies have revealed its unexpected presence on cultural heritage artifacts, such as ancient manuscripts, paintings, sculptures, photograph, and textiles [78,79]. The presence of this fungus on such objects poses new challenges for conservators and researchers due to its ability to degrade cellulose and produce lipolytic enzymes [80].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, more marine bacteria begin to grow, feeding on the remains of archaea and the attacked collagen matrix. Gradually, more and more bacteria and fungi can colonise, causing the collagen to break down so that the manuscripts begin to disintegrate [ 24 , 147 ]. Another research group held Actinobacteria and Aspergillus species responsible for the appearance of the purple spots.…”
Section: Paleogenomics and Metagenomics Analysesmentioning
confidence: 99%
“…The smaller peptides obtained can then be analysed using mass spectrometers and assigned to the corresponding proteins with the help of matching to databases. The disadvantage of this approach is that complete sequence coverage can often not be achieved and that fragments with post-translational modifications (PTMs), protein truncations, as well as alternative splicing events cannot be identified [ 13 , 147 , 168 ]. In the top-down approach, intact proteins are analysed so that proteoforms can also be characterised.…”
Section: Paleoproteomics and Metaproteomics Analysesmentioning
confidence: 99%